Automobile usage and urban rail transit expansion: evidence from a natural experiment in Beijing, China. (17th February 2016) - Xie, Lunyu
Abstract: Using individual travel diary data collected before and after a rail transit expansion in urban Beijing, the impact of urban rail accessibility improvement on the usage of rail transit, automobiles, buses, walking and bicycling, as well as the cross-area externality induced by congestion alleviation, is estimated. The results show that rail transit usage significantly increased for commuters residing in the affected areas and that the additional rail passengers were previously auto users, rather than bus passengers. The cross-area externality is estimated as small, which implies that the congestion alleviation was not large enough (yet) to change the travel mode choices of commuters residing in areas that did not experience the improvement. Furthermore, the results show that neither the number of commute work trips nor their length increased, indicating that the quantity of travel was not increased by the rail transit expansion.